Closing the Gender Gap in African Agriculture in the Face of Climate Change - African Group of Negotiators Expert Support (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Gender is not about ‘women and girls’ but about roles, responsibilities, access and control over resources and relations between men and women, boys and girls which are socially ascribed. Women’s meaningful participation in decision-making requires going beyond the presence of more women in institutions and processes. Comprehensive gender analyses at national and local levels are necessary to identify the challenges and opportunities for developing gender-responsive agricultural policies. A Gender Action Plan (GAP) for agriculture with a well-structured and robust M&E system is essential. Strengthening Gender Management Systems in the agriculture sector with regular gender audits can promote greater equity between women and men.